XYLOSE ISOMERASES FROM THERMOTOGALES - B. Fatima; Z. Hussain (Journal of Animal and Plant Sciences, 2015)
Biotechnology has been directed primarily towards reproductive technology been employed for improvement of industrial important enzymes which are foremost concern over the years for researchers. This review paper discusses the exciting scientific and technical advances in molecular biology for the genetic improvement in thermotogales, the hyperthermophiles with respect to xylose isomerase to meet the industrial demands. A thermo-acid stable enzyme possesses neutral or slightly acidic pH optima and a higher affinity for glucose have a potential for industrial applications for the production of high fructose corn syrup (HFCS). Xylose isomerases from Thermotoga sp are class II enzymes, utilize a 1, 2 hydride shift catalytic mechanism, active only in the presence of Mn+2, Co+2 and Mg+2 . Recombinant xylose isomerases from T. neapolitana existed both as homodimer as well as homotetramer have been produced under mesophilic fermentation conditions, with a maximal activity at 97°C. Mutant enzyme in addition to this catalytically active at pH 5.5 and showed 3.1 fold increased catalytic efficiency towards glucose. The addition of the carbohydrate biding domain to Thermotoga’s xylose isomerase successfully immobilized the enzyme to chitin beads. The turnover numbers (kcat) for glucose to fructose conversion for both unbound and immobilized mutants was greater than the wildtype enzyme.
Keywords: xylose isomerases; thermotogales; hyperthermophiles